Pengaruh Financial Stability, External Pressure dan Operational Risk terhadap Pendeteksian Kecurangan Laporan Keuangan - Putri, Kendra Aulia Husna; Astuti, Christina Dwi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to examine the effect of financial stability, external pressure, and operational risk on fraudulent financial statements. The population in this study are 27 Banking companies listed on the Indonesian Stock Exchange (IDX) website in the 2019-2022 period. The sample in this study was selected based on the purposive sampling method. Based on predetermined criteria, a total observations of 108 was obtained. The analytical technique used in this study was multiple linear regression. The results of the analysis show that financial stability has a positive effect on fraudulent financial statements, external pressure has no effect on fraudulent financial statements, and operational risk has no effect on fraudulent financial statements.